Hepatopulmonary syndrome - Fahed-Inigo, George P.; Torres-Palacios, Alfonso; Rodríguez-Cintrón, William (Puerto Rico Health Sciences Journal, 2007)
This is a report of a 56-year-old male who was admitted to the Intensive Care Unit of the San Juan V.A. Medical Center with altered mental status and severe hypoxemia. He was diagnosed with severe hyponatremia and hepatopulmonary syndrome.